The comparative evaluation of the preparedness and development of graduates - Bakos-Tóth, Eszter (Acta Agraria Debreceniensis, 2009)
The skill of dealing with people was given a special importance by the persons interviewed during my examination by means of questionnaires although most of the specialist works I consulted did not pay too much attention to this fact. When asked about the particular fields of further studies, only a small proportion of the respondents regarded the development of their personality important. I think to dissolve this paradox is necessary as without the development of personality it is impossible to improve interpersonal skills, that is one of the basic pillars of good performance at work. Regarding that it is the graduates who fill managerial posts, dealing with people belongs to one of their tasks. Among the respondents if the first degree were from a college and not from a university, the greatest proportion of those studying further would live in Heves and Borsod-Abaúj-Zemplén counties. However, this connection cannot be proved in Budapest. Individual motivation is the main drive of studying further after obtaining a degree in a greater and greater proportion. The graduates’ studying further is significantly directed to acquiring extra knowledge rather than a totally new profession and they get a deeper insight into the knowledge necessary for their profession driven by their own motivation.